Modeling Of Hybrid EDFA/DRA For Long Haul Optical Fiber Communication System - Hossain , Nadir (2007)
This research work focuses on the modeling of hybrid EDFA/DRA for long haul optical fiber communication system (OFCS). The mathematical model of hybrid EDFA/DRA is represented by two separate models. The first model deals with the modeling of double pass (DP) Erbium doped fiber amplifier (EDFA) and the second model deals with the modeling of distributed Raman amplifier (DRA). These two models are integrated in order to model the hybrid EDFA/DRA.